2009
DOI: 10.1111/j.1540-5907.2009.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Partisan Conflict on Congressional Approval

Abstract: Partisan divisions in American politics have been increasing since the 1970s following a period where scholars thought parties were in decline. This polarization is observed most frequently within the debates and deliberation across issues within Congress. Given that most studies of public opinion place the behavior of elites at the center of public attitudes, surprisingly little research examines the effect of partisan conflict on the mass public. This research examines quarterly congressional approval data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 49 publications
3
89
0
Order By: Relevance
“…And positive media coverage predicted public approval, r(193) = 0.26, P < 0.001. Media coverage explained the link between Congressional language and public approval, B = 1.82, 95% confidence interval (CI) = [0.31, 5.04] in a mediation analysis (SI Text) (18). In addition to an indirect effect via media coverage, a direct effect of Congressional language on public approval remained, B = 36.30, 95% CI = [29.05, 43.55], suggesting that the direct (C-SPAN) and indirect (media) channels may work in tandem to explain how Congressional language influences public opinion.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…And positive media coverage predicted public approval, r(193) = 0.26, P < 0.001. Media coverage explained the link between Congressional language and public approval, B = 1.82, 95% confidence interval (CI) = [0.31, 5.04] in a mediation analysis (SI Text) (18). In addition to an indirect effect via media coverage, a direct effect of Congressional language on public approval remained, B = 36.30, 95% CI = [29.05, 43.55], suggesting that the direct (C-SPAN) and indirect (media) channels may work in tandem to explain how Congressional language influences public opinion.…”
Section: Significancementioning
confidence: 99%
“…A second explanation is that the public disapproves of ineffective governance. For example, public approval of Congress tends to drop when Republicans and Democrats are polarized against one another and when Congress conflicts with the President (4,5). We test a third explanation that has less to do with action and more to do with talk (6).…”
mentioning
confidence: 99%
“…Research has also tied low public approval of Congress to the inability of the membership to live up to the public's overall expectations (Kimball & Patterson, 1997) and the institution's tendency to engage in largely unpopular-although democratic-political processes, such as extensive debate, excessive partisanship, conflict, and compromise (Binder, 2003(Binder, , 2015Doherty, 2015;Durr, Gilmour, & Wolbrecht, 1997;Hibbing & Theiss-Morse, 1995, 2002Mann & Ornstein, 2006, 2012Ramirez, 2009;Sinclair, 2011). Also, recent computerized sentiment analysis has linked the decline of prosocial language on the floor to the erosion of congressional approval over time (Frimer, Aquino, Gerbauer, Zhu, & Oakes, 2015).…”
Section: Chaptermentioning
confidence: 99%
“…Ramirez (2009) concluded that the public's desire to mitigate procedural partisan conflict among legislators is more important than the substance of policy actions. Harbridge and Malhotra (2011) find partisan conflict reduces public support for Congress, but also note that the partisan public responds favorably to their own representatives who act in a partisan manner.…”
Section: The Legislative Process and Public Opinion Toward Congressmentioning
confidence: 99%
See 1 more Smart Citation